Assessment of the hydrogeoecological state of the Pripyat river basin - Vovk, Oleksandr P.; Polyansky, Serhiy V; Shut, Bohdan V (Cognum Publishing House, 2025)
This article highlights the principal directions of research concerning surface and groundwater within the Prypiat River basin. The groundwater monitoring network is currently in a critical state. Insufficient and delayed funding of hydrogeological programs has resulted in the decline of systematic groundwater observations. The natural functioning of the basin is further disrupted by the ongoing military conflict in Ukraine caused by the armed aggression of the Russian Federation. As surface water pollution continues to increase, groundwater is expected to play a growing role in water supply due to its generally better quality and higher natural protection from contaminants. Nevertheless, under strong anthropogenic influence, groundwater remains vulnerable to degradation. Such circumstances threaten Ukraine’s overall ecological security and underline the urgent need to modernize national water monitoring and management systems in line with the EU Water Framework Directive.
Keywords: 556.3:504.06(477.82)